Excited oscillons and charge-swapping - A. Alonso-Izquierdo; D. Canillas Martínez; T. Romańczukiewicz; K. Sławińska; A. Wereszczyński (Journal of High Energy Physics)
Abstract We show that the charge-swapping phenomenon can be understood as a real valued oscillon carrying an excitation in imaginary direction in the target space. Furthermore, we introduce a two dimensional collective model which quantitatively captures the charge swapping dynamics.